IMPROVING THE ENERGY EFFICIENCY OF HEAT PUMP UNITS (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
In the world, traditional energy resources are depleting and the ecological burden on the environment is increasing, so production from existing energy sources will solve the problem. So, this paper investigates the energy performance of an autonomous solar-assisted heat pump (HP) system designed for heating and cooling applications in rural regions with a sharply continental climate, such as Uzbekistan. The proposed integrated system combines a network of solar thermal collectors, a hot-water storage tank and a mechanically driven heat pump. Solar radiation is absorbed in the collector field and stored as medium-temperature water, which is then used as a stable low-potential heat source for the evaporator. A thermodynamic model of the heat pump cycle was developed based on heat and mass balance equations, compressor isentropic efficiency and logarithmic mean temperature difference in the evaporator and condenser. Hourly ambient air and storage-tank temperatures were obtained for the heating season; ambient air varies between 7÷15 °C, whereas storage temperature is maintained between 3÷40 °C. The coefficient of performance (COP) of the conventional air-source HP was compared with that of the solar-assisted configuration. Numerical results show that the average COP increases from 4.1 for the basic HP to 6.2 for the HP with solar collectors, corresponding to an efficiency gain of about 50 %. The findings demonstrate that solar-assisted heat pumps can significantly reduce electricity consumption and greenhouse-gas emissions in decentralized heating systems.